Loans or grants? - Daniel Cohen; Pierre Jacquet; Helmut Reisen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
In this paper we examine whether absorptive capacity can constitute sufficient justification for rejecting the proposal of a large aid increase to support the `big push'. We argue that the probability of a poverty trap exists for many countries, in particular the least developed countries (LDCs) and that an increase in aid is relevant for them. Moreover we show that the decrease in marginal aid returns is slower in vulnerable countries, which supports the rationale to include vulnerability as one of the aid-allocation criteria. We examine the main obstacles to absorptive capacity, such as disbursement constraints and short-term bottlenecks, macroeconomic problems, including loss in competitiveness and macroeconomic volatility, as well as the weakening of institutions. The general conclusion that we draw for reconciling the two approaches is that absorptive capacity strongly influenced by aid itself or by its modalities. The big push and absorptive capacity approaches cannot be reconciled without aid reform supported by an aid increase. First, what is needed is to balance the utilization of aid between activities that are directly productive and those that are social in nature in order to avoid transitory loss of competitiveness. Second, schemes that facilitate the use of aid as insurance against exogenous shocks are to be enhanced because they lower the risk of Dutch disease, and contribute to faster and more equitable growth over the long term. Finally a performance-based conditionality should replace the traditional policy-based one in order to cope with several absorptive capacity limitations, particularly the sociopolitical one. An aid-supported big push will not be effective without new ownership of policy by the recipient countries.
Keywords: F35; O40; 330; absorptive capacity; big push; aid effectiveness; poverty trap; institutions; Entwicklungshilfe; Entwicklungshilfekonditionen; Kredit; Kreditrisiko; Schuldenerlass; Ökonometrisches Modell; HIPC (Heavily Indebted Poor Countries)